2013
DOI: 10.1039/c3cp50609f
|View full text |Cite
|
Sign up to set email alerts
|

Staying hydrated: the molecular journey of gaseous sulfur dioxide to a water surface

Abstract: A water surface is a dynamic and constantly evolving terrain producing a vast array of unique molecular properties and interactions with chemical species in the environment. The complex dynamics of water surfaces permit life on earth to continue, but also complicate the development of a complete microscopic picture of the specific behaviors that take place within interfacial aqueous environments. This computational study examines a piece of the water puzzle by elucidating the bonding, dynamic interactions, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…■ RESULTS AND DISCUSSION Benchmark Test. The hydration behavior of SO 2 at the air−water interface was previously investigated by Richmond and co-workers, 30 using the BOMD simulation (based on the B3LYP hybrid functional) with the water layer containing 24 water molecules. Here, the same system is employed to reproduce previous simulation results.…”
Section: ■ Computation Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…■ RESULTS AND DISCUSSION Benchmark Test. The hydration behavior of SO 2 at the air−water interface was previously investigated by Richmond and co-workers, 30 using the BOMD simulation (based on the B3LYP hybrid functional) with the water layer containing 24 water molecules. Here, the same system is employed to reproduce previous simulation results.…”
Section: ■ Computation Methodsmentioning
confidence: 99%
“…To gain more insight into the SO Oppenheimer molecular dynamical simulations to investigate the hydration structure of SO 2 . 30,33 Both studies reported variability of the SO 2 hydrate structures. However, to our knowledge, few studies concerning the effects of water droplet sizes on SO 2 solvation have been reported, which could have important atmospheric implications because different sizes of droplets exist during the aerosol nucleation and growth process in the atmosphere.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An efficient interfacial surface reaction may be the combined result of a lower activation energy under acidic conditions at the air-water interface, preferred molecule orientation resulting from the water structure right at the air-water interface, and a variation in reactivity with pH on the aquated aerosol surfaces. [7][8][9][38][39][40]…”
Section: -mentioning
confidence: 99%